Morphological Characteristics and Mechanical Properties of Quarry Dust Waste as Sand Replacement in Mortar - Jumahat, Aidah; Yosri, Nur Fatin Amira M; Hashim, Ummu Raihanah; Mohd Sidek, Mohd Norhasri; Haris, N. A. (International Journal of Integrated Engineering, 2024)
The generation of industrial waste has been steadily increasing, necessitating sustainable waste management strategies. Quarry dust, a by-product of the aggregate production process obtained from crushing rocks in rubble crusher units, contributes to this waste stream. This study proposes using fine quarry dust waste, ranging from 50 to 100 ?m, as an additive or replacement in mortar to mitigate environmental and health hazards caused by this kind of waste. However, literature on the usage of very fine quarry dust waste (about 50-100?m particle sizes) as a partial sand replacement in mortar production is very limited. Therefore, this paper presents an experimental investigation on the effects of incorporating quarry dust waste as a sand replacement, with variations of 0%, 5%, 10%, 15%, 20%, 25%, and 30%, with a water-cement ratio of 0.5 to enhance mortar strength. The micro-structural analysis and compression tests were performed to evaluate the mortar samples. XRF analysis confirmed that silica oxide (SiO2) was the predominant element present in quarry dust waste. The compression tests were conducted on 50 mm x 50 mm x 50 mm mortar cubes. The tests were performed at 3, 7, 14, and 28-day intervals. The results revealed that, incorporating 25% quarry dust waste as a sand replacement produced the highest compressive strength of about 37 MPa on the 28th day curing duration. Hence, using this material as an environment-friendly sand replacement offers a promising solution for producing high-strength mortar. This finding highlights the potential of quarry dust waste as a supplemental cementitious material and emphasizes its viability in reducing the environmental impact associated with industrial waste.